1999
DOI: 10.1021/bi981915h
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Ile1 Changes the Mechanism of Streptokinase:  Evidence for the Molecular Sexuality Hypothesis

Abstract: Plasminogen (Plgn) is usually activated by proteolytic cleavage of Arg561-Val562. The new N-terminal amino group of Val562 forms a salt bridge with Asp740, creating the active protease plasmin (Pm). However, streptokinase (SK) binds to Plgn, generating an active protease in a poorly understood, nonproteolytic process. We hypothesized that the N-terminus of SK, Ile1, substitutes for the N-terminal Val562 of Pm, forming an analogous salt bridge with Asp740. SK initially forms an inactive complex with Plgn, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
107
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(117 citation statements)
references
References 29 publications
10
107
0
Order By: Relevance
“…However, the maximal level of these bursts was approximately half of that observed with natural SK prepared from S. equisimilis (data not shown). It has been demonstrated recently that a free Nterminal residue (Ile) (34) and some flanking residues (35) are required for the auto-activation of HPG by SK. However, the positive NPGB reaction of nSK, albeit less than that of natural SK, was easily explained when N-terminal sequence analysis of program.…”
Section: Resultsmentioning
confidence: 99%
“…However, the maximal level of these bursts was approximately half of that observed with natural SK prepared from S. equisimilis (data not shown). It has been demonstrated recently that a free Nterminal residue (Ile) (34) and some flanking residues (35) are required for the auto-activation of HPG by SK. However, the positive NPGB reaction of nSK, albeit less than that of natural SK, was easily explained when N-terminal sequence analysis of program.…”
Section: Resultsmentioning
confidence: 99%
“…Studies demonstrating a critical role of the N terminus of SK in conformational activation support the "molecular sexuality" mechanism (34,56,57). In this mechanism, insertion of the SK N terminus into the N-terminal binding cleft in the Pg catalytic domain and salt bridge formation with Asp 194 (chymotrypsin numbering) triggers the activating conformational change.…”
Section: Discussionmentioning
confidence: 96%
“…However, in the presence of plasmin, SAK and SK mechanisms are indistinguishable (12). In the present experiments, active site generation by SUPA was examined under classical experimental conditions where excess acylating agent was present to inhibit trace amounts of plasmin (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…By analogy to the activation of tissue Pg activator, which has significantly greater activity as a zymogen than Pg, it has been suggested that the binding of ␥-domain to the autolysis loop of Pg induces the formation of a critical intramolecular salt bridge between Lys 698 and Asp 740 of Pg that productively structures the activation domain (11). Another hypothesis ("molecular sexuality") states that SK nonproteolytically activates Pg when the NH 2 -terminal isoleucine-1 (Ile 1 ) of the ␣-domain forms a salt bridge with Asp 740 of Pg (12). In this activation sequence, which is typical of the zymogens of the chymotrypsinogen family, salt bridge formation productively restructures the latent activation domain (14).…”
mentioning
confidence: 99%